Trajectory Tracking Control for a Wheeled Mobile Robot Using Fractional Order PIaDb Controller - Tawfik, Mouwafak A.; Abdulwahb, Emad N.; Swadi, Salah M. (Al-Khwarizmi Engineering Journal, 2014)
Nowadays, Wheeled Mobile Robots (WMRs) have found many applications as industry, transportation, inspection, and other fields. Therefore, the trajectory tracking control of the nonholonomic wheeled mobile robots have an important problem. This work focus on the application of model-based on Fractional Order  PIaDb (FOPID) controller for trajectory tracking problem. The control algorithm based on the errors in postures of mobile robot which feed to FOPID controller to generate correction signals that transport to  torque for each driven wheel, and by means of dynamics model of mobile robot these torques used to compute the linear and angular speed to reach the desired pose. In this work a dynamics model of mobile robot was driven for the case where the centroid  of mobile robot platform is not coincide with reference frame of mobile robot (i.e. reference frame is located at midpoint of driven wheels axis), while the inertia is counted for. The Evolutionary Algorithm has been used to modified the parameters (Kp, Kd, Ki,a, and b) of the FOPID controller for wheeled mobile robot. Simulation results show the effectiveness of the proposed control algorithm: that is demonstrated by applied this controller at four case studies (Circular trajectory, S-shape trajectory, Infinity trajectory, and Line trajectory at two cases, with presences of disturbance and without), these results shows good matching between desired trajectory and simulation one while error in posture goes to zero rapidly.